A CASE HISTORY ON THE PHENOMENAL CORROSION OF MARINE PROPELLERS IN FISHING BOATS - BALASUBRAMANYAN, R (Fishery Technology, 2016)
Although high tensile brassess of copper-zinc alloys (Manganesebronze) find extensive use in all marine applications, underaggressive sea-water, marine propellers cast out of such an alloyfrequently suffer heavy corrosion damages due to dezincification.An interesting case history where a number of propellers haveundergone dezincification in the Cochin back-waters is narrated inthis paper.